ELABORATION AND INVESTIGATION OF THE ADAPTING DEVICES FOR SOME TRACKS OF THE SATELLITE LASER-LOCATION STATIONS - Denishchik, Yu. A.; Mel’kov, S. M. (Одеські астрономічні публікації, 2017)
The reshaper of nanosecond impulses is described, as device of concordance of receivers of laser radiation with the subnanosecond measuring device of temporal intervals in the laser location stations.